Ver-o-Peso: poesia em postais do[s] submundo[s] - OLIVEIRA, Raphaella Marques de (Universidade Federal do Pará, 2017)
This research value the hazard and daily meetings. motivated by an biographical experience through the labyrinths of Ver-o-peso – the biggest free market of Latin America, located in city of Belém and regarded as a great landmarks – there I’ve been met persons who aren’t live in landmarks, but makes daily the narratives behind of history [!] artistically, this paper is situated as a work of poetry and form a colecttion of articles about the esthetics experiencies lived in Ver-o-Peso. [this also a intuitive work inspiraded by brasilians poet]. scientifically, it cross the fields of Arts, Philoshophy and Comunication Research and use ethnographic methodogies and the rhizome, the philosophical concept. [:] together, Art and Science, makes this notebook an reunion of words written under the officials narratives about Ver-o-Peso. what they say and not say print poetic narrative cards.